2020
DOI: 10.1038/s41467-020-17400-4
|View full text |Cite
|
Sign up to set email alerts
|

Future changes in the trading of virtual water

Abstract: Water stressed regions rely heavily on the import of water-intensive goods to offset insufficient food production driven by socioeconomic and environmental factors. The water embedded in these traded commodities, virtual water, has received increasing interest in the scientific community. However, comprehensive future projections of virtual water trading remain absent. Here we show, for the first time, changes over the 21 st century in the amount of various water types required to meet international agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…where represents the VW flux traded from country i to country j, and is the weighted flux. This weighting methodology has been utilized by Lenzen et al [12] who, however, apply only the physical water scarcity weight, while we apply the composite water scarcity weight that includes also economic water scarcity.…”
Section: Single Fluxes Of Scarcity-weighted Virtual Watermentioning
confidence: 99%
See 2 more Smart Citations
“…where represents the VW flux traded from country i to country j, and is the weighted flux. This weighting methodology has been utilized by Lenzen et al [12] who, however, apply only the physical water scarcity weight, while we apply the composite water scarcity weight that includes also economic water scarcity.…”
Section: Single Fluxes Of Scarcity-weighted Virtual Watermentioning
confidence: 99%
“…In the first one, authors address the question on whether VW trade compensates or not for lack of available resources (including water and land) for food production in given countries or areas [8,9,10]. Many scholars find evidence that VW trade alleviates pressure on several water stressed regions, which are allowed to import and consume food that has been produced in other world regions where water is more abundant [12,16,50,51,52,53]. On the other hand, other authors identify some paradoxes since some water-scarce countries or areas actually are net VW exporters, and vice versa [13,14,54,55,56].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both KSA and UAE have limited self-sufficiency in domestic production, most notably lacking in food and agriculture, with imported food products representing more than 80% of total food requirements 25 . Both the countries are classified as critically dependant on the Virtual Water Trade Network, whereby embodied water is gained through food imports 26,27 .…”
Section: Ai Sectors That Contribute Most To the Countries' Gdpmentioning
confidence: 99%
“…However, as of today some models have been successfully used in nexus studies where also climate is considered an important system as much as energy, water and land Daher and Mohtar (2015). The most recent studies incorporating all CLEW sectors have shown that restricted bilateral perspectives (and models) omit important feedback and should therefore be updated with comprehensive methodologies Graham et al (2020); Vinca et al (2020a).…”
Section: Introductionmentioning
confidence: 99%